Transfer-catalyst-free biomimetic asymmetric reduction of 3-sulfonyl coumarins with a regenerable NAD(P)H model. Issue 24 (7th March 2022) - Zhu, Zhou-Hao; Ding, Yi-Xuan; Zhou, Yong-Gui
Abstract : A novel transfer-catalyst-free biomimetic reduction of 3-sulfonyl coumarins with the chiral and regenerable NAD(P)H model CYNAM has been developed, affording the 3-sulfonyl dihydrocoumarins with excellent enantioselectivities. Abstract : A novel transfer-catalyst-free biomimetic reduction of the tetrasubstituted olefins 3-sulfonyl coumarins with the chiral and regenerable [2.2]paracyclophane-based NAD(P)H model CYNAM has been developed, affording chiral 3-sulfonyl dihydrocoumarins with excellent enantioselectivities.